The Future of Minorities in Post-ISIL Iraq (Raparin Journal of Humanities (RJH), 2021)
The period after June 2014 has seen forces from the Islamic State of Iraq and the Levant (ISIL), an armed group, spread quickly across Iraq. This process has led to massive displacements in which affected over two million people. Indeed, the primary targets of ISIL have been religious and ethnic minorities. Some of these groups include Yazidis, Shabak, Kaka’i, and Christians. Also, ISIL has abducted or injured many people, with thousands also killed. Examples of adverse actions that the armed group has committed include severe human rights abuses such as the looting of property, the abduction of children, the destruction of places of worship, sexual enslavement, rape, forced conversion, and summary executions. Whereas the period before the insurgency group’s entry still witnessed minorities exist as a vulnerable group, the violence led by ISIL has threatened to eliminate them permanently from regions such as the Nineveh Plains, have lived in these areas for several centuries. The main question purpose of this paper is to examine the future status of minorities in post-ISIL Iraq? ISIL. I will argue that although ISIL had been defeated in Iraq, their impact will be critical on Iraqi Minorities Even after the demise of ISIL. Currently, informal settlements, abandoned buildings, and camps in which the displaced persons live reflect deteriorating humanitarian conditions. With international agencies experiencing limited resources and also the government failing to offer an effective response, most of the international displaced people (IDPs)[1] do not have enough shelter, health care, water, food, and other essential items. Indeed, most vulnerable groups include children and women. At a time when the majority are contemplating emigration out of Iraq, their survival in the immediate and far future rests upon collaboration among four groups that include the international community, the Iraqi government, Kurdish authorities, and minorities themselves. Some of the specific areas that need to be addressed include the asylum dilemma, reconciliation and restoration, preventing future abuses, legislation, and humanitarian issues.